Network-Based Equity Evaluation of Tsunami Evacuation Access for a Megathrust Scenario in Palabuhanratu: English - Sudibyo, Reno; Kurniadi, Anwar; Subiyanto, Adi; Ramadhan, Fajar Gilang (Pusat Penelitian dan Pengembangan BMKG, 2025)
We present a network-based equity evaluation of tsunami evacuation access for a megathrust scenario in Palabuhanratu, quantifying both individual safety attainment and the spatial distribution of access. By overlaying physics-based inundation data with a road graph, we compute multimodal time-to-safety and isochrones, summarizing village-level access through overall reachability (RR), Gini, and hazard-weighted Gini (Gini*) indices. Evacuation time allowances (ETAs) are set at 22, 18, and 15 minutes—validated against site-specific arrival modeling and real-world departure observations from the 2024 Noto event—revealing a critical temporal tipping point. While an ETA of 22 minutes ensures total reachability (RR=1.00) with low inequality, tightening the window to 18 and 15 minutes sharply reduces RR and increases Gini* scores. Furthermore, the addition of an alternative Tsunami Evacuation Area (TEA) at Smile Hill yields localized time savings and minor gains in specific clusters at 22 minutes, yet provides no systemwide benefit at shorter ETAs, indicating that time scarcity dominates access during tight windows. Methodologically, this study employs